Collaborative Estuarine Management: A Study on Cochin Estuary - K.T., Thomson; M.A., George (Fishery Technology, 2025)
This paper provides basic information for guiding the task of managing estuaries in South India at different levels of public and private partnership using the insights drawn from primary studies on the dynamics of various resource management practices in selected fishing villages. The necessary data were collected during 2004-05 using frame surveys, participatory research methodologies and structured questionnaires. The study revealed that the management practices in the study villages exhibited a blend of both informal (communitybased) and formal (state-centric hierarchical) governance. Collaborative management practices replaced community-based and state-centric management strategies, produced cooperative solutions to resource crisis and livelihood vulnerability of traditional fishing communities. The study also confirmed the active presence of decentralised collaborative fisheries management systems under certain situations. The analysis revealed that, since complex multiple commons like estuaries are not easily predictable, traditional knowledge systems and practices should be recognized as baseline information for building institutions and resource management policies.